LIQUID SMOKE PERFORMANCE OF LAMTORO WOOD AND CORN COB - Fronthea Swastawati; Tri Winarni Agustini; Y S Darmanto; Eko Nurcahya Dewi (JOURNAL OF COASTAL DEVELOPMENT, 2007)
Smoking of fish by using liquid smoke is already needed to be implemented in Indonesia, as it could produce a high quality and safe smoked fish products. Various wood and agricultural wastes are possible to be used as raw material of liquid smoke. The aimed of this research was to explore the liquid smoke performance of Lamtoro wood as a representative of hard wood and liquid smoke of Corn cob as representative of agricultural wastes which contain of anti oxidative and bactericidal component processed by dry distillation method with the temperature reach to ± 400ºC. The results showed that chemical composition of the two liquid smoke have their own specification. Phenolic compounds of each liquid smoke were: 481,2 ppm (Lamtoro); 335 ppm (Corn cob) . pH value: 3 (Lamtoro) ; 2,9 (Corn cob). Both of liquid smoke found not containing of carsinogenic Benz (a) Pyrene, but Lamtoro was contain Benz (ghi) Peryle in a small amount: 1,869 ppm.